Numerical prediction of the ductile damage in single point incremental forming process. (October 2017) - Said, L. Ben; Mars, J.; Wali, M.; Dammak, F.
Highlights: Deformation mechanism and damage evolution in ISF process are investigated. a coupled anisotropic plasticity and continuum ductile damage models is adopted. A VUMAT is employed to implement the material behavior. Capability of the FE modeling to predict the material deformation process is investigated. Abstract: The incremental sheet forming (ISF) is a flexible forming technology in the sheet metal engineering. This process reaches a higher formability of manufactured sheets than conventional sheet metal stamping process. A deep insight into parameters influencing this process is crucial for more understanding of the process. This paper presents a numerical investigation of damage mechanism during the Single Point Incremental sheet metal Forming (SPIF) of a part with conical shape. An elasto-plastic constitutive model with quadratic yield criteria of Hill'48 and mixed isotropic/kinematic hardening behavior is adopted to simulate ISF operation. A user material subroutine (VUMAT) is employed to implement the material behavior of the sheet metal. The efficiency of the finite element model to predict the material deformation process is investigated by comparing numerical and experimental results. A comparison between two hardening models in terms of deformed shape after springback and thickness evolution is presented. Damage evolution is investigated by comparing the results of two hardening models. The final part is devoted to study the influence of some process parameters on the damage evolution and forming effort during the SPIF of studied parts.